DESIGNING SAMPLES OF READNG COMPREHENSION MATERIAL FOR TEACHING NARRATIVE TEXTS - Tapun, Fenansius L.; Marbun, Rismaya; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : The aim of this research was to find out the appropriate reading comprehension material samples designed for teaching narrative texts. This research was conducted to the second semester of eleventh grade students of SMAK Talino Sungai Ambawang in academic year 2014/2015. The method of this research is development research. The participants were taken from class XI IPS that consisted of 32 students and an English teacher . The data were collected by using observation, questionnaires and interview. Based on the data analysis, the result of the observation checklist showed that most of the students were motivated and involved actively during the teaching learning process. The result of the teacher?s interview after implementation showed that the reading comprehension material samples designed by the writer are appropriate for the students. As the conclusion, according to the teacher?s and students? feedback of the questionnaires the level of reading comprehension material samples designed by the writer had fulfilled the 3 aspects in designing the material and appropriate for the students. Keywords: Designing, Reading Comprehension, Narrative Texts Abstrak : Penelitian ini bertujuan untuk menemukaan contoh rancangan materi tentang pemahman membaca yang cocok dipakai dalam mengajar teks naratif. Penelitian ini dilakukan pada siswa semester dua kelas XI IPS di SMAK Talino Sungai Ambawang pada tahun akademik 2014/2015. Metode yang dipakai pada penelitian ini adalah pengembangan penelitian. Peserta dari penelitian ini di ambil dari siswa kelas XI IPS yang terdiri dari 32 siswa dan juga guru pelajaran bahasa Inggris dari sekolah tersebut. Data di peroleh dengan menggunakan pengmatan, wawancara. Berdasarkan analisis data, hasil pengamatan menunjukan bahwa siswa termotivasi dan aktif selama proses belajar mengajar. Sedangkan berdasarkan hasil wawancara terhadap guru bahasa Inggris menunjukan bahwa contoh materi pemahaman membaca yang dirancang oleh penulis cocok dipakai untuk siswa. Kesimpulannya, berdasarkan tanggapan guru dan siswa dari hasil angket yang disebarkan bahwa contoh materi yang dirancang oleh penulis telah memenuhi 3 aspek dalam merancang materi dan cocok untuk siswa. Kata Kunci : Merancang, Pemahaman Bacaan, Teks Naratif